MODERN ASPECTS OF THE ACTIVITY OF A TEACHER'S ASSISTANT IN AN INCLUSIVE EDUCATIONAL ENVIRONMENT - Kopchuk-Kashetska, Maria; Tsiuniak, Oksana; Dovbenko, Svitlana (Mountain School of Ukrainian Carpaty, 2023)
The article explores the role and importance of a teacher's assistant in an inclusive educational environment for children with special educational needs. It focuses on the current trends and challenges faced by teaching assistants in working with this category of students. The key aspects of the role of a teacher's assistant, such as individualization of learning, promotion of social integration and psychosocial support, are indicated. Particular attention is paid to the use of technology and innovation in providing effective support to children with different educational needs, and the issue of accessibility of technology for all students, regardless of their individual limitations or needs, is also addressed. Emphasizes the interaction of the teacher's assistant with other participants in the educational process, such as parents, teachers and other professionals, and the importance of teamwork and exchange of experience to achieve optimal results in the upbringing and education of children with special educational needs. It considers the challenges and prospects for the development of inclusive education in the modern educational environment, identifies ways to improve the training and support of teacher assistants. The study serves as an important source of information for educators, researchers and practitioners working in the field of inclusive education. Conclusions are drawn and prospects for further research and development of methods aimed at optimizing the role of the teacher's assistant in an inclusive educational environment are proposed. Effective support for the learning and development of children with special educational needs remains an urgent and important task, and the article makes an important contribution to understanding this issue in the modern educational context.